Hubungan Pemerintah Pusat dengan Pemerintah Daerah dalam Kerangka Pengelolaan Keuangan Negara dan Daerah - Telly Sumbu (Fakultas Hukum Universitas Islam Indonesia, 2010)
The state and district financial management is an important part in the governmental arrangement in Indonesia. To decide the problem of state and district financial status, it should be placed in the context of constitutional and governmental system which is followed in Indonesia. The problem that would like to be investigated is how is the relation between the central government and district government in the frame of state and district financial management. This research used the investigation of normative law. The approach method used was jurisdiction. The data compiling is conducted through literacy study. In this research, the compiled material would be qualitatively analyzed. The result of this research has concluded that the basic law in applied the state and district financial management is different. However, both are still in an inseparable relation since both are conducted in the frame of Negara Kesatuan Republik Indonesia (United nation of Indonesia Republic).Key words : State finance, district finance